2008
DOI: 10.1118/1.2938521
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight sensor for respiratory motion gating

Abstract: In this technical note we present a system that uses time-of-flight (ToF) technology to acquire a real-time multidimensional respiratory signal from a 3D surface reconstruction of the patient's chest and abdomen without the use of markers. Using ToF sensors it is feasible to acquire a 3D model in real time with a single sensor. An advantage of ToF sensors is that their high lateral resolution makes it possible to define multiple regions of interest to compute an anatomy-adaptive multidimensional respiratory si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 9 publications
2
48
2
Order By: Relevance
“…2a). Schaller et al presented a ToF-based system to acquire a low-dimensional respiratory signal [21]. Lately, similar systems using Microsoft Kinect have been presented by Xia et al and Alnowami et al [22,23].…”
Section: Positioning and Motion Management In Radiation Therapymentioning
confidence: 99%
“…2a). Schaller et al presented a ToF-based system to acquire a low-dimensional respiratory signal [21]. Lately, similar systems using Microsoft Kinect have been presented by Xia et al and Alnowami et al [22,23].…”
Section: Positioning and Motion Management In Radiation Therapymentioning
confidence: 99%
“…Recently, it has been demonstrated that respiratory motion can be effectively monitored using real-time 3D surface imaging [3]. Schaller et al [4] presented a time-of-flight respiratory motion detection system that estimates at the ToF frame rate of 25 fps two 1D-signals for the thorax and abdomen movement, respectively. Fayad et al [5] proposed to use ToF as surrogate to develop a respiration model using PCA.…”
Section: Introductionmentioning
confidence: 99%
“…Based on ρ, the radial distance (range) r from the sensor element to the object can be computed as r = cρ 4πf mod where f mod denotes the modulation frequency and c the speed of light. The technology has recently been proposed for diagnostic, interventional and therapeutic medical applications such as patient positioning [9] and respiratory motion detection [4]. However, due to physical limitations of the sensor, depth data from ToF cameras are subject to high temporal noise and exhibit systematic errors.…”
Section: Introductionmentioning
confidence: 99%
“…used for AR applications (Koch et al, 2009). In the context of biomedical applications ToF cameras have been used as an imaging modality for respiratory motion gating (Schaller et al, 2008) and patient positioning (Placht et al, 2012;Schaller et al, 2009) in radiotherapy as well as for building patient-specific respiratory motion models Wentz et al, 2012).…”
Section: State-of-the-artmentioning
confidence: 99%